Serious workplace violence against health-care workers in China: synthesising a profile of evidence from national judgment documents. (October 2018) - Cai, Ruilie; Tang, Ji; Deng, Chenhui; Lv, Guofan; Pan, Jay
Abstract: Background: Health-care workers have a high risk of being involved in patient-initiated workplace violence around the world. In China, workplace violence is a concern, as it not only causes physical and psychological harm on health-care workers, but also limits the development of the health-care industry and system. The absence of prevention guidelines and related laws and regulations on this issue presents a barrier to the prevention of workplace violence. We therefore aimed to report a profile of serious workplace violence against health-care workers and explore the violence initiators' features in China. Methods: We collected data from the China Judgement Online system. We searched judgment documents using three search terms: "criminal case", "healthcare institution", and "healthcare worker". Judgement date was limited to between Jan 1, 2013, to Dec 31, 2016. The severity of workplace violence was judged by the criminal law regulation—ie, only the cases violating the criminal law would be enrolled. The primary outcome was to synthesise a profile of evidence for serious workplace violence against health-care workers in China. Descriptive analysis was used to investigate the occurrence, risk degree, and related factors of serious workplace violence. Findings: Between Jan 1, 2013, and Dec 31, 2016, 459 criminal cases (with 680 violence initiators in total) about patient-initiated workplace violence against health-care workers in China were reported. The number of cases of workplace violence varied substantially among provinces, with the east region having the highest reported numbers. Emergency departments in secondary hospitals were the most common place for medical workplace violence. Doctors were at higher risk of workplace violence than other health-care workers, and violence initiators were mainly male farmers with low educational qualifications that were aged 18–44 years. Causes of death-related issues, specifically including those "consider[ed] as medical malpractice after death", "just because of death", and "compensation negotiation fails after death", and dissatisfaction with the outcome after treatments were the most frequent reasons for workplace violence against health-care workers. Interpretation: Workplace violence is widely distributed among provinces and institutions of China. Corresponding provinces and institutions might need to make targeted improvements, such as putting forward contingency plans and improving medical quality. Key findings from this study have policy implications that could be prioritised by policy makers to improve the guidelines of preventing workplace violence against health-care workers and establish laws and regulations to protect health-care workers' rights in China. Funding: National Natural Science Foundation of China (grant number71303165 ), Ministry of Education of China (18YJA790062 ), Sichuan University (grant number2015SCU04A19 and 2018SCUH0027 ), andChina Medical Board (grant number17-276 ).